On the Common Development of Ideological and Political Work and Enterprise Management - Yao, Liang (Journal of Theory and Practice of Management Science, 2023)
With the rapid development of social economy and culture, the party building and ideological and political work of state-owned enterprises have also undergone significant changes. By strengthening party building work and innovating employee ideological and political work, we can effectively promote the high-quality development of state-owned enterprises. With the deepening of enterprise reform, the issue of innovative party organization construction is becoming increasingly prominent. To fundamentally solve these problems, only by continuously improving enterprise party building and ideological and political work, providing clear direction for the development of grassroots party building in enterprises, can we enhance the enthusiasm and creativity of enterprise ideological and political workers, and ensure the high-quality implementation of grassroots party building and ideological and political work.